Ultradian rhythms in the transcriptome of Neurospora crassa - Ananthasubramaniam, Bharath; Diernfellner, Axel; Brunner, Michael; Herzel, Hanspeter (iScience, 2018)
In many organisms, the circadian clock drives rhythms in the transcription of clock-controlled genes that can be either circadian (∼24-hr period) or ultradian (<24-hr period). Ultradian rhythms with periods that are a fraction of 24 hr are termed harmonics. Several harmonic transcripts were discovered in the mouse liver, but their functional significance remains unclear. Using a model-based analysis, we report for the first time ∼7-hr third harmonic transcripts in Neurospora crassa, a well-established fungal circadian model organism. Several third harmonic genes are regulated by female fertility 7 (FF-7), whose transcript itself is third harmonic. The knockout of circadian output regulator CSP1 superimposes circadian rhythms on the third harmonic genes, whereas the knockout of stress response regulator MSN1 converts third harmonic rhythms to second harmonic rhythms. The 460 ∼7-hr genes are co-regulated in two anti-phasic groups in multiple genotypes and include kinases, chromatin remodelers, and homologs of harmonic genes in the mouse liver.